2007
DOI: 10.1016/j.cca.2006.12.017
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of Lens culinaris agglutinin-reactive thyroglobulin ratio in serum for distinguishing benign from malignant conditions of the thyroid

Abstract: Background: Traditionally, the follow-up of differentiated thyroid carcinoma consists of periodic withdrawal from L-T4-suppressive therapy to allow performance of a highly sensitive serum Tg measurement to detect recurrences. In this study, Lens culinaris agglutinin-reactive thyroglobulin ratios in serum were investigated to evaluate in usefulness for detection of thyroid carcinoma.Methods: The study was conducted on 93 serum sample from 23 healthy volunteers, 32 patients with benign thyroid tumor, 28 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…In addition, several other assays have been developed to distinguish Tg produced by malignant and benign thyroid tissues, but they have not been applied for routine use (12). Until more reliable methods become available, we recommend that every laboratory should monitor TgAb interference of the used Tg method.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several other assays have been developed to distinguish Tg produced by malignant and benign thyroid tissues, but they have not been applied for routine use (12). Until more reliable methods become available, we recommend that every laboratory should monitor TgAb interference of the used Tg method.…”
Section: Discussionmentioning
confidence: 99%
“…Structure elucidation of Tg glycosylation in cancer has not been performed to date but may be useful for thyroid cancer diagnostics. Preliminary studies showed that the interaction of lectin LCA with Tg from thyroid carcinoma was significantly lower than that in normal thyroid tissue and in patients with benign thyroid tumor [ 111 , 112 ]. The percentage of LCA-reactive Tg could discriminate between benign and malignant lesions [ 113 ].…”
Section: Clinically Approved Biomarkersmentioning
confidence: 99%
“…The percentage of LCA-reactive Tg could discriminate between benign and malignant lesions [ 113 ]. It was also found that the percentage of LCA-reactive Tg was significantly decreased in thyroid carcinoma patients who were positive for lymph node metastasis compared to thyroid carcinoma patients who were negative for lymph node metastasis [ 112 ].…”
Section: Clinically Approved Biomarkersmentioning
confidence: 99%
“…During malignant transformation, epithelial cells modulate the glycosylation profile of their secretion proteins and these post-translational changes may represent specific markers which may be useful diagnostic or prognostic tools. The composition of carbohydrate chains on thyroglobulin from thyroid carcinoma has been reported to differ from that in normal thyroid tissue (Maruyama et al, 1998;Shimizu et al, 2007a). Shimizu et al (2007b) investigated Lens culinaris agglutinin (LCA)-reactive thyroglobulin ratio in serum to evaluate its usefulness for distinguishing between thyroid carcinoma and benign thyroid tumor.…”
Section: Thyroglobulinmentioning
confidence: 99%